Ways to live history. Or philosophy, culture, and architecture in the origins of the museum Altes in Berlín - Lemos, Fabiano (Education Policy Analysis Archives, 2011)
From the beginnings of what we now know as our modernity, man has been surprised with his own finitude. The 18th and 19th century bourgeois needed to formulate complex ways of preserving the past and of linking with it. In the philosophes’ circle, time concept starts to double itself in the idea of origin, that, for them, had become opaque. We just need to think of the broad-range process of structuring museums and restructuring natural history collections in cities such as Paris and Berlin, around the turn to the 19th century, so that we can be convinced that the surprise with that origin that one cannot recognize anymore, that becomes object of popular and scientific interest, leads each and all of the decisions in this process. Museum is just one of the institutions in which man, through a complex series of idealizations of space, show himself the spectacle of a lost time and, thus, of a culture whose educational thrive can only be understood by associating to these institutions. Our task is to investigate – and the case study of the grounding of the Altes Museum in Berlin, between 1822 and 1830, will perform this concretely – which educational policy made the emergence of this new ideological model possible, and , on the opposite way, which conceptual elaborations confirmed or legitimated the new pragmatic topography of time in modernity within the institution that had as aim, precisely, articulate and administrate past and memory.